The Role Of Motor Rehabilitation And Sensory Education In Adapted Physical Activity For People With Cerebral Palsy - Abdullah Mohsin, Alaa (International Journal of Psychosocial Rehabilitation, 2020)
Cerebral palsy is a neurological disease that causes a physical defect that develops and leads to a physical disability during the stages of human development and this occurs in different parts of the body related to the performance of motor functions, hence the importance of motor rehabilitation, which contributes to strengthening the person’s skill and increasing the level of motor and functional efficiency that gives the patient a kind of independence and self-reliance, as kinetic rehabilitation is one of the most important means of physical therapy, which is concerned with the body and the way to provoke its movements in order to maintain functional work and rehabilitate muscle tissue after injury, Movement therapy is one of the most effective natural treatments, especially if it is used in an organized, accurate and consistent manner with the dysfunction of the body, due to its reliance on the concepts and laws of kinesiology in building therapeutic systems to restore and renew the motor functions of all parts of the body, especially the dependence of the main part of rehabilitation on the performance of exercises Which aims to maintain flexibility and muscle strength, prevent joint and bone deformities, and sensory stimulation to reorganize the functions of motor neurons. In addition to the exercises associated with the process of muscle contraction is a specialist physiotherapist assesses the movement and balance the other hand, the specialist Alartfinu all exercises for training kinesthetic and recommend the training needed by the injured at each age stage and selection of devices The assistance he needs, and both help the injured to adapt to his disability and give him sensory and motor experience. Physiotherapy helps him learn the best ways of movement and bodily balance, and then help the injured to stand and walk naturally or by using assistive prosthetic devices. It is known that strengthening muscles and reaching the normal range of motion for joints is the basis In this research, we will present a set of exercises and adapted motor exercises that help the person with cerebral palsy to reach a good level of motor flexibility.